1986
DOI: 10.1002/bit.260280402
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption of Thiobacillus ferrooxidans on coal surfaces

Abstract: The adsorption of Thiobacillus ferrooxidans to coal surfaces has been studied. Adsorption experiments were conducted on coal samples from eight different Eastern coal fields. In all cases the adsorption process was at least 90% complete within the first two minutes following inoculation. The results of these experiments were used to test the validity of two proposed adsorption models. The first model assumes that bacterial adsorption follows second-order irreversible kinetics of the second kind with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Selective adhesion of T. ferrooxidans to pyrite and its interactions. The selectivity of T. ferrooxidans adhesion to pyrite was first suggested when it was observed that the cells adhered to pyrite within coal particles (3,8). The same phenomenon was observed in iron-rich areas of sulfide ores (9).…”
Section: Discussionmentioning
confidence: 78%
“…Selective adhesion of T. ferrooxidans to pyrite and its interactions. The selectivity of T. ferrooxidans adhesion to pyrite was first suggested when it was observed that the cells adhered to pyrite within coal particles (3,8). The same phenomenon was observed in iron-rich areas of sulfide ores (9).…”
Section: Discussionmentioning
confidence: 78%
“…Evidence for this type of mechanism has also been presented for the adsorption of Thiobacillus ferroxidans to coal surfaces. The bacterium is held at a finite distance from the surface by the combination of repulsion and attraction, and from that point can dissociate or can either form covalent bonds or expend energy to synthesize polymers that will hold it permanently to the surface (Bagdigian and Myerson, 1986). Similarly, insulin has been found to bind to fat cells reversibly at first until a conformation change in the receptor causes desorption to occur at a much slower rate (Lipkin et al, 1986).…”
Section: Discussionmentioning
confidence: 98%
“…Previously coal attachment via biofilms (Raudsepp et al., 2015, Hazrin-Chong and Manefield, 2012) and direct cell interactions (Hazrin-Chong et al., 2014, Bagdigian and Myerson, 1986, Chen and Skidmore, 1988) has been observed for microbes grown on coal aerobically, whereas little examination of this phenomena has been made for native anaerobic microbial consortia (Vick et al., 2016). Here, distinct attached communities of microbes were seen in all three coal communities, whereas scanning electron microscopic visualization of the coal surface identified biofilm formation in only Surat Basin microcosms.…”
Section: Discussionmentioning
confidence: 99%